Mineral status of soils, forages and cattle in Nicaragua. I. Microminerals - Velásquez Pereira, Juan; McDowel, Lee; Conrad, Joseph; Wilkinson, Nancy; Martin, Frank (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
A study was conducted to determine the micromineral status of cattle in six important cattle-producing regions of Nicaragua. A total of 14 farms within six regions during the wet season and eight farms within two regions during the dry season were evaluated. States in each region were: I (Esteli), II (Leon and Chinandega), III (Managua). IV (Granada and Rivas), V (Boaco and Chontales), and VI (Matagalpa and Jinotega). On each farm, 14 composite soil and forage samples and 30 blood samples (lactating cows, heifers and calves) were collected and analyzed for micromineral concentrations. Soil Mn was different (P Ë‚ .05) among regions in the wet season. Soil Cu was higher (P < .05) and Mn and Zn lower (P < .05) in the wet season. Region III showed the highest frequency of soil samples deficient in Fe (< 2.5 ppm), Cu (< 0.3 ppm) and Zn (< 2.5 ppm) in the wet season. In the dry season, soil Cu and Fe deficient samples were higher in region IV. Forage Cu (< 8 ppm), Zn (< 30 ppm) and Co (< 0.1 ppm) deficient samples were close to 100 %, indicating that supplementation of these microminerals may be needed across all regions. Forage Mn was higher (P < .05) in region V than in other regions, except for region II. Percentage of samples below the critical level (< 40 ppm) ranged from 24 to 100 % in the wet season and 86 and 17 % for regions IV and V respectively, in the dry season. Forage samples deficient in Se (< 0.2 ppm) were less than 50 % among regions, except for region V in the dry season (87 %). Percentage of forage Se and Zn samples were lower and higher, respectively, in the wet season. No differences among regions and animal classes were found in serum Cu and Zn. Serum Se was lower (P < .05) in calves than heifers in the dry season. Percentage of serum samples deficient in Se (Ë‚ 4 μg/ 100 mL) ranged from 13 to 93 % in the wet season. Serum Cu (Ë‚ 50 μg/100 mL) deficient samples ranged from 0 to 43% in the wet season. Region IV showed the highest frequency of serum Zn (Ë‚ 60 μg/100 mL) deficient samples (50 %).